Fixed point theorems of new generalized C-conditions for (psi; gamma)-mappings in modular metric spaces and its applications - Gündoğdu, Hami; Öztürk, Mahpeyker; Gözükızıl, Ömer Faruk (Nonlinear Analysis: Modelling and Control, 2023)
This paper introduces new generalizations of the C-condition for (ψ; γ)-mappings in modular metric spaces. We extend the fixed point results for such mappings yielding the generalized C-condition in metric spaces to modular ones.We proved the existence and uniqueness of solutions in modular metric spaces for these kinds of mappings. We give an example to emphasize that our results work in the difference between modularmetric spaces and usual ones. Moreover, we consider some initial and boundary value problems to support the results obtained here. We examine the existence and uniqueness of the solutions for the problems in modular metric spaces.